Beyond the Herald Patch: Clinicohistological Correlation of Clinical Variants of Pityriasis Rosea - Chaitra N; Asha G S; Harsha G; Nagesh T S (International Journal For Multidisciplinary Research, 2026)
Pityriasis rosea (PR) is a common acute papulosquamous disorder characterized by a classical presentation as well as several atypical clinical variants. Atypical presentations may create diagnostic difficulty and may require histopathological assessment for differentiation from other papulosquamous disorders. This study evaluated the clinical spectrum and clinicohistological features of PR.